The sources of stress amongst construction consultants in workplace environment / Nurul Afida Isnaini Janipha and Faridah Ismail. - Janipha, Nurul Afida Isnaini; Ismail, Faridah (Universiti Teknologi MARA Cawangan Selangor, 2018)
Designers in Malaysia are beginning to feel the existence and growing of stress levels at the workplace due to high pressure and competitive working environment. Designer profession is to create inspire designs that sometimes lead to stress and affect their work performance. Moreover, stress can cause poor planning, lack of communications and interpersonal conflicts. Therefore, the objective of this paper is to identify the causes and effects of workplace stress amongst designers. Questionnaire survey was distributed among 500 designers. The respondents are from construction consultant companies in Klang Valley. The response rate of this paper was performed of about 38% of the samples. The outcome of this research show that they were generally enjoyed their work but sometimes feel stress due to poor planning and job demand, working surrounding and relationship among staff. This indicates that stress lead to bad designs and sometimes gives bad effects to the performance of the designers.